A baseline study on the Mini-coconut Oil Mill Project for Small Coconut Farmers Development - de los Santos, Levi O.,Jr
The main objective of this study, is to generate data that will determine and describe the socio-economic profile of the Leon Small Coconut Farmers Organization members. Respondents of this study involves 30 active members of LSCFO who were randomly selected. They are mostly male with with an average age of 45 years and are married. Their educationaal attainment is in high school with a medium level of aspiration. Coconut farming is their primary occupation, average farm size they till is almost 1 hectare. Majority of them own the farm they cultivate. Their average annual production i 625 kilograms. They have an average monthly income of P 4, 059 for an average of six-member household with an average monthly expenditure of P 3,144, respondents have an above average standard of living.